The Influence of Community Participation, Clarity of Budget Targets, and Internship Control System on Accountability of Village Fund Management in Nusa Penida District - I Putu Adi Arya Winata (E-Jurnal Akuntansi, 2025)
The amount of village funds allocated by the central government has increased from 2015 to 2019. Accountability is needed in managing village funds of this size. The study was conducted to determine the effect of public participation, clarity of budget targets, and internal control systems on the accountability of village fund management in Nusa Penida District. Respondents in this study were 64 people who were selected using the saturated sample method (census). Data collection was carried out using a questionnaire. The data collected were analyzed using multiple linear regression analysis. The results of this study indicate that the variables used have a positive and significant effect on the accountability of village fund management in Nusa Penida District. This means that the higher the public participation, the clarity of budget targets, and the internal control system, the better the accountability of village fund management.